ZAKAT SEBAGAI SARANA BANTUAN BAGI MASYARAKAT BERDAMPAK COVID-19 - Saputra, Hijrah (Al-Ijtima`i: International Journal of Government and Social Science, 2020)
The Signing of a National Disaster (Covid-19) as a National Disaster through Presidential Decree Number 12 of 2020 Determination of Non-Disaster in the Spread of Covid-19 as a National Disaster. All efforts that are being made right now are being carried out by the government through social measures to distribute the outbreak virus, of course, it will have an impact on the community in taking the call. The "Simalakama" option. Staying at home incapacitated, supported, then threatened with death. Or get out of the house to make a living to meet the needs of the family, threatened by the coronavirus, then threatened with death. This study discusses the role of zakat as a means of helping people who consider Covid-19. The research method used is descriptive qualitative data collection from articles, media, and libraries. The results of this study To overcome this Co-19 pandemic, zakat becomes one of the means to help people who face this disaster. Even the government through the Indonesian Ulema Consultative Council (MUI) has issued its fatwa so that zakat mal can be issued as soon as possible and must wait for a full year, as well as the nature of zakat issued at the end of Ramadan can be issued at the beginning of Ramadan. Thus, asking for zakat can be adjusted to the people who need assistance in this Covid-19 epidemic.